Dancing on the moon : short stories about AIDS / Jameson Currier. - Currier, Jameson. (Viking, 1993)
In the title story from Dancing on the Moon a young man, thinking of all his friends who have died from AIDS and those who are ill, says: "No one out there has a clue as to what our lives are like. All this is as strange to them as dancing on the moon." The speaker marveling at the gulf that separates those affected by AIDS from a world that thinks itself immune is just one of the memorable characters in this unprecedented book of twelve virtuoso stories about the impact.